The Impact of Macroeconomic Factors and Banking Management on Bank Deposit Attraction in Iran: Evidence from the Generalized Method of Moments Panel Approach - Montazeri Shourekchali, Javad; Fattahi, Majid; Bagheri, Seyed Mohammad (Management Strategies and Engineering Sciences, 2024)
Given the growth in the number of private banks in Iran over the past decades, competition among banks to attract resources and deposits has increased. To maintain profitability and sustain their position in the banking industry, banks must focus on customer satisfaction and offer services that align with customer needs. Accordingly, and considering the importance of identifying the factors influencing the attraction of bank deposits for decision-makers in the field of banking management in the country, this study aims to identify the factors affecting the attraction of bank deposits in Iran during the period from 2011 to 2022 using the panel Generalized Method of Moments (GMM) approach. The findings of this study indicate that among the macroeconomic factors affecting the attraction of bank deposits, inflation and macroeconomic instability have a positive effect on attracting transactional deposits (including current accounts, savings accounts, and other deposits) but a negative effect on attracting investment deposits (including long-term and short-term investments). Meanwhile, national income and interest rates have a negative effect on transactional deposits and a positive effect on investment deposits. Furthermore, among the banking variables affecting bank deposit attraction, the quality of electronic services, customer clubs, and the Return on Equity (ROE) of banks have had a positive and significant impact on the growth of both transactional and investment deposits.